2018
DOI: 10.1371/journal.pone.0201143
|View full text |Cite
|
Sign up to set email alerts
|

Association between blood eosinophil count and risk of readmission for patients with asthma: Historical cohort study

Abstract: BackgroundRecent studies have demonstrated an association between high blood eosinophil counts and greater risk of asthma exacerbations. We sought to determine whether patients hospitalized for an asthma exacerbation were at greater risk of readmission if they had a high blood eosinophil count documented before the first hospitalization.MethodsThis historical cohort study drew on 2 years of medical record data (Clinical Practice Research Datalink with Hospital Episode Statistics linkage) of patients (aged ≥5 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 32 publications
2
26
0
3
Order By: Relevance
“…Another marker evaluated in our study is FENO. This is a validated and specific biomarker for T2-driven airway inflammation in asthma and its use in the clinical assessment of asthma is recommended by Guidelines from the American Thoracic Society [28]. In our study, FENO levels are significantly higher in current asthma compared to controls as we expected.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Another marker evaluated in our study is FENO. This is a validated and specific biomarker for T2-driven airway inflammation in asthma and its use in the clinical assessment of asthma is recommended by Guidelines from the American Thoracic Society [28]. In our study, FENO levels are significantly higher in current asthma compared to controls as we expected.…”
Section: Discussionsupporting
confidence: 78%
“…Blood eosinophil count is an established biomarker in asthma. A high blood eosinophil count correlates with poor asthma control and with an increased risk of severe exacerbations and hospitalizations [26][27][28]. Another marker evaluated in our study is FENO.…”
Section: Discussionmentioning
confidence: 66%
“…At the same time concomitant comorbidities, such as obesity or psychiatric conditions, may negatively affect the perception of the functional improvement due to the treatment. Higher eosinophil count has also been related to a more severe disease 11 , but the individual intrinsic variability of this parameter 12 has to be taken into account. Likewise, the effect on the quality-of-life is controversial 3 , being perhaps more relevant in allergic asthma.…”
mentioning
confidence: 99%
“… 33 , 34 A recent historical cohort study investigated the relationship between high blood eosinophil counts (≥350 cells/µL) and hospital readmission in 2613 patients with asthma hospitalized for acute exacerbation. 35 Results showed that a high blood eosinophil count in the year before asthma-related hospitalization is associated with an increased risk of readmission within the following year. 35 A secondary diagnosis of asthma was present in 26% of the patient population with no difference between the high and low eosinophil groups.…”
Section: Limitationsmentioning
confidence: 97%
“… 35 Results showed that a high blood eosinophil count in the year before asthma-related hospitalization is associated with an increased risk of readmission within the following year. 35 A secondary diagnosis of asthma was present in 26% of the patient population with no difference between the high and low eosinophil groups. Among the subgroup of patients with COPD who had a secondary diagnosis of asthma, the association of blood eosinophil count with all-cause readmission in the univariable analysis was not significant, and patients with a secondary diagnosis of asthma had similar readmission rates compared to those without asthma.…”
Section: Limitationsmentioning
confidence: 97%